Combining synergetic control and super twisting algorithm to reduce the active power undulations of doubly fed induction generator for dual-rotor wind turbine system - Benbouhenni, Habib; Lemdani, Soufiane (Національний технічний університет "Харківський політехнічний інститут", 2021)
This work presents the amelioration ofdirect power control using synergetic-super twisting algorithms for asynchronous generators integrated into dual-rotor wind turbine systems. Method.The main role of the direct power control is to control the active and reactive powers and reduce the harmonic distortion of stator current of asynchronousgenerator for variable speed dual-rotor wind turbine systems. The traditional strategyis more attractive due to its high efficiency and simple algorithm. Super twisting algorithms are a non-linear command strategy; characterized by robustness against the parameters change or disturbances, it gives a good power quality under different conditions such as changing generator parameters. Novelty. Synergetic-super twisting algorithms are designed. Synergetic-super twisting algorithms construction is based on synergetic command and super twisting algorithms in order to obtain a robust control strategy and a fast system with acceptable precision. We use in our study a 1.5 MW asynchronous generator integrated to dual-rotor wind turbine system in order toregulate the active and reactive powers. Results.As shown in the results figures using synergetic-super twisting algorithms the ameliorate performances especially minimizes the torque, active and reactive power undulations, and reduces harmonic distortion of stator current (THD = 0.19 %) compared to traditional strategy.

Робота представляє вдосконалення безпосереднього регулювання потужності за допомогою синергетичих алгоритмів супер-скручування для асинхронних генераторів, інтегрованих у системи вітряних генераторів з подвійним ротором. Метод. Основна роль безпосереднього регулювання потужності полягає у керуванні активною та реактивною потужностями та зменшенні гармонічних спотворень струму статора асинхронного генератора для вітряних генераторів з подвійним ротором зі змінною швидкістю обертання. Традиційна стратегія є більш привабливою завдяки її високій ефективності та простому алгоритму. Алгоритми супер-скручування – це нелінійна командна стратегія; характеризується стійкістю до зміни параметрів або порушень, це забезпечує хорошу якість енергії в різних умовах, таких як зміна параметрів генератора. Новизна. Розроблені синергетичні алгоритми супер-скручування. Побудова алгоритмів синергетичного супер-скручування базується на алгоритмах синергетичних команд та супер-скручування, для того щоб отримати надійну стратегію керування та швидку систему з прийнятною точністю. У нашому дослідженні ми використовуємо асинхронний генератор потужністю 1,5 МВт, інтегрований в систему вітряних турбін з подвійним ротором для регулювання активної та реактивної потужностей. Результати. Як показано на рисунках з результатами, із використанням алгоритмів синергетичного супер-скручування, покращені характеристики особливо мінімізують крутний момент, коливання активної та реактивної потужності та зменшують гармонічні спотворення струму статора (THD = 0,19%) порівняно з традиційною стратегією.
Keywords: asynchronous generator; direct active and reactive power command; асинхронний генератор; команда прямої активної та реактивної потужності